RANCANG BANGUN ALAT UKUR KEKERUHAN AIR BERBASIS MIKROKONTROLER - Eka Nuzula, Nike; Endarko, Endarko (BERKALA FISIKA, 2013)
Turbidity meter based on microcontroller has succesfully been designed and fabricated. The photodiode as sensor and a LED as light source were used for measuring level of waterturbidity whereas microcontroller ATMega 8535 was used for data processing. The turbidity levelof water is measured based on Nephelometer method. The LED and photodiode detector were positioned parallel to each other at a distance of 2 inches. The measurement results indicated that the turbidity meter could be used to measure the turbidity level of water in the range 0 – 200 NTUand the maximum of standard deviation was at 1.33 NTU.Keywords : Turbidity, NTU, Photodiod, LED, Nephelometer